Quantum Algorithms for Quantum Fourier Transform Used in Quantum Information Theory - Vasile – Laurentiu DOSAN; Elena-Corina CIPU (Communications of International Proceedings, 2020)
In this work, we describe Quantum Fourier Transform (QFT) which basically is a Discrete Fourier Transform (DFT). It’s main application is phase estimation, an essential part in Shor’s algorithm used in Quantum Computation. We gave a brief introduction about the mathematical language of Quantum Information Science for implementation circuits on QFT and inverse QFT using IBM Quantum Experience and we did an approximation of QFT.
Keywords: discrete Fourier transform; Quantum Fourier transform; Quantum Computing; Shor’s algorithm.